THE IMPACT OF INTERACTIVE ACTIVITIES ON ENGLISH LANGUAGE IN CLASSROOM SETTINGS - Aliyorova Shohsanam (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article explores the significance of incorporating interactive activities in English classes to enhance language learning and engagement. With a focus on the field of language education, this study addresses the growing importance of interactive pedagogical approaches in fostering effective language acquisition. By identifying the gap in current research regarding the impact of interactive activities on English language proficiency, this paper aims to investigate the role of such activities in promoting student participation and motivation. Utilizing a qualitative research methodology, this study examines the effectiveness of interactive activities in improving language skills and fostering a communicative classroom environment. The key findings reveal that interactive activities not only enhance language learning outcomes but also contribute to students' overall language proficiency and confidence. This research underscores the significance of integrating interactive elements into English language instruction to create dynamic and engaging learning experiences that benefit students' language development. Interactive activities play a crucial role in English classes by fostering student engagement and promoting active participation. These activities provide opportunities for students to practice language skills in a dynamic and engaging way, enhancing their communication abilities. By incorporating interactive elements such as group discussions, role-playing, and interactive games, teachers can create a more immersive learning environment that encourages students to interact with each other and apply their language knowledge in real-life scenarios. Ultimately, this study highlights the importance of interactive activities in English classes as a valuable tool for promoting active learning and enhancing language proficiency in diverse educational settings.